Replacing An Extracted Natural Tooth As A Pontic By Using Fiber-Reinforced Composite: A Case Report: A Case Report - Haq, Sabana; Ahmed, Alia; Khan, Dania; Rizwan, Zarnab; Sajid, Khadija; Zahid, Aqsa (Journal of Rawalpindi Medical College, 2024)
Summary: Losing an anterior tooth could be extremely devastating for the patient and to address the psychological and emotional trauma of the patient, quick replacement is crucial. A contemporary conservative choice is a Fiber-Reinforced composite bridge. The current case report describes the fractured permanent mandibular left lateral incisor which needed to be extracted followed by the replacement of the same natural tooth crown as a pontic using Fiber-reinforced composite (Ribbond). The results were satisfying to the patient, both aesthetically and functionally. Long-term follow-up studies are needed to further evaluate this treatment option in the future. Keywords: tooth, denture design, composite resins